PELATIHAN ECOPRINT UNTUK KELUARGA PENYANDANG DISABILITAS - Kurniati Zainuddin; Haerani Nur; Faradillah Firdaus; Rohmah Rifani; Dian Novita Siswanti (Jurnal Kebajikan: Pengabdian Kepada Masyarakat, 2023)
People with disabilities can be trained to be productive with a number of skills, but training individuals with disabilities apparently requires more strenuous effort and takes longer. Therefore, parents or families can take a role in optimizing it. Batik is a product that has high selling value and is quite easy to make. Providing batik and ecoprint training to families with disabilities is an effort to empower families, and these skills can also be taught to families with disabilities.